2021
DOI: 10.3846/jbem.2021.15655
|View full text |Cite
|
Sign up to set email alerts
|

Stock Liquidity and Corporate Trade Credit Strategies: Evidence From China

Abstract: This study investigates the nexus of stock liquidity and trade-credit policies in China from 2002 to 2017. The estimates are robust to alternative proxies, various fixed-effects, and the exogenous impact of Chinese split share structure reforms (SSSR) 2005-06 is investigated through the difference-in-difference analysis. The results validate that stock liquidity significantly impacts firms’ capacity to produce more trade credit supplies and less reliant on trade credit demand. The study applied SUEST analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 81 publications
1
9
0
1
Order By: Relevance
“…Nonetheless, the impact of stock liquidity on trade credit is still growing body of knowledge, particularly, in the emerging markets. Most recent studies in this field are Abdulla et al (2017), Shang (2020), Islam et al (2022) and Shahzad et al (2022). The focus of these studies either is mainly China markets or cross countries studies that draw general insights from various countries.…”
Section: Stock Liquiditymentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, the impact of stock liquidity on trade credit is still growing body of knowledge, particularly, in the emerging markets. Most recent studies in this field are Abdulla et al (2017), Shang (2020), Islam et al (2022) and Shahzad et al (2022). The focus of these studies either is mainly China markets or cross countries studies that draw general insights from various countries.…”
Section: Stock Liquiditymentioning
confidence: 99%
“…Recently, Shahzad et al (2022) examined the stock liquidity and firms' trade strategy in China and reported the firms' stock liquidity lead to more extension of credit to customers and less likely to depend on suppliers for the demand of trade credit. More comprehensively using emerging market cross-countries study, Islam et al (2022) found that firms use less credit when their assets are liquid.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Por su parte, Shahzad et al (2022) concluyeron que los formuladores de políticas deben centrarse en la liquidez del mercado porque eleva la capacidad de las empresas para movilizar capital a través de disposiciones de crédito comercial; el aspecto micro de este estudio sugiere que la liquidez de las acciones permite a los gerentes diseñar estrategias competitivas sin precios y evitar el uso excesivo de créditos comerciales. En Reino Unido, Vanteeva & Hickson (2021) concluyeron que las empresas se beneficiaron con los préstamos gubernamentales a largo plazo, particularmente después de las crisis financieras y de los términos de intercambio.…”
Section: Introductionunclassified
“…Stock liquidity affects financial stability [7], [8]. It also impacts the financial structure and cost of capital [9], [10], the dividend distribution policy [11], and the risk of corporate failures [12], [13].…”
Section: Introductionmentioning
confidence: 99%